ANALISA TEGANGAN CHAIN LINE SINGLE POINT MOORING TYPE CATENARY ANCHOR LEG MOORING PADA AFRAMAX TANKER - Nurhuda Yusuf; Wirawan Husodo Adi; Sumardiono Sumardiono (Proceedings Conference on Marine Engineering and its Application, 2018)
One of the constraints that occur in the mooring system of SPM is the breaking of chain line caused by its inability to accept work load.In this problem, it is necessary to analize the tension line of SPM catenary anchor leg mooring (CALM) type on aframax tanker. The purpose of this research is to know the movement response of structure and the maximum tension chain line. The largest response amplitude operator (RAO) obtained when SPM moored on Aframax Tanker in the conditions of translational movement heave by 0.986 (m/m) on heading of 0° and 135 º. The largest response of the structure obtained when SPM moored on Aframax Tanker in the conditions of translational movement heave by 17.44 m²/(rad/s) on heading of 180 º. The greatest tension chain line is 2424873 N with the results of chain line tension still meets the safety factor in accordance with the standard API RP 2SK 2nd edition. The analysis results of chain line power structure is 155.42 MPa, if the dimension of chain line is reduced by 0,2 mm/year in a space of 13 year time then the stress obtained is 169,67 Mpa, and with estimation of 30 year time the value of stress obtained is 238,82 Mpa.